A dynamic analysis on implementing performance excellence model: Importance, achievement and correlations. (November 2016) - Wen, Decheng; Lv, Jie; Chen, Xiao; Dai, Ting
Highlights: Implementing PEM can promote organization's improvement of achievement level (AL). Organization's opinion on importance level (IL) is different with the PEM criteria. The improvement rate of AL is in partial positive correlation with IL. The improvement of process helps to improve the financial results. Abstract: Performance excellence model (PEM) has become an important management pattern for many years in the world. In 2004, China issued two national standards of PEM. But at present, most researches on PEM are based on the static data on some certain time, in this way there lacks systematic research on its dynamic changes features, including the improvement of PEM implementation, the impacts of process improvement towards results improvement, etc. Hence this article conducts a research on the improvements of items' achievement levels of PEM implementation, the relationship between the improvements and items' importance levels, and the impacts of process improvements towards financial results. Through the researches on the Government Quality Award (GQA) recipients in Shandong province and Anhui province, it is found that those recipients have gained improvements with different levels in terms of item's achievement after PEM implementation and the achievement level is in positive correlation with its importance. Besides, under the control of achievement level before PEM import, the improvement rate of achievement is also in positive correlation with its importance. Moreover, the improvement of process helps to improve the financial results and each 1% increase in the process's improvement rate of achievement level per year on average will lead to a 0.605% increase in the annual improvement rate of financial results. Organization's opinion on importance level is different with the PEM criteria. And the point value gap among process categories should be narrowed down.